Предмет: Математика, автор: мип1

решите уравнения:(4,2x + 3,1) - (0,7x - 2,7) = 6,85       - (2,5x - 2,5) - (3,1x - 3,1) = - (1,6 - 1,6x)            (3,1x + 3,1) - (1,8x + 1,8) = 1,6x + 1,6


 

Ответы

Автор ответа: Stas96
0

(4,2x+3.1)-0,7x+2.7=3.5x+5.8=3.5x=-5.8

                                                  x=5.8/3.5

                                                  x=1/66

Автор ответа: liliya23
0

1)4,2х+3,1-0,7х+2,7=6,85

3,5х+5,8=6,85

3,5х=6,85-5,8

3,5х=1,05

х=0,3

2)-2,5х+2,5-3,1х+3,1=-1,6+1,6х

 -5,6х+5,6=1,6+1,6х

 -7,2х=-7,2 

х= 1

3)3,1х+3,1-1,8х-1,8=1,6х+1,6

1,3х+ 1,3=1,6х+1,6

-0,3х=0,3

х=-1 

 

 

Похожие вопросы
Предмет: Алгебра, автор: azizmurodov2204